2021
DOI: 10.1111/apha.13631
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine and vascular dysfunction

Abstract: Cigarette smoking is the single most important risk factor for the development of cardiovascular diseases (CVDs). However, the role of nicotine, the addictive component of all tobacco products, in the development of CVD is incompletely understood. Although increased public awareness of the harms of cigarette smoking has successfully led to a decline in its prevalence, the use of electronic cigarettes (e‐cig) or electronic nicotine delivery system has increased dramatically in recent years because of the percep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 138 publications
0
24
0
1
Order By: Relevance
“…Similarly, CD31 22,50 , was also increased following exposure to e-Cig aerosol with nicotine, perhaps as part of the compensatory mechanism. The determinant factor for these results appears to involve the presence of nicotine, which has been shown to have pro-angiogenic properties 14 . Nicotine exhibits dose-dependent impacts on endothelial cell homeostasis and exhibits angiogenic effects that may be responsible for the pathogenesis of diseases like atherosclerosis 16,51,5 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, CD31 22,50 , was also increased following exposure to e-Cig aerosol with nicotine, perhaps as part of the compensatory mechanism. The determinant factor for these results appears to involve the presence of nicotine, which has been shown to have pro-angiogenic properties 14 . Nicotine exhibits dose-dependent impacts on endothelial cell homeostasis and exhibits angiogenic effects that may be responsible for the pathogenesis of diseases like atherosclerosis 16,51,5 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported the presence of carbonyl compounds in e-Cig aerosols, notably: formaldehyde, acetaldehyde and acrolein, as well as long-chain and cyclic alkanes and alkenes 12 . Additionally, trace amounts of metals have been reported, such as aluminium, barium, chromium and cadmium within the e-Cig aerosol 13,14 . These chemicals are known to be harmful and cytotoxic, causing pulmonary and cardiovascular stress 15 .…”
Section: Introductionmentioning
confidence: 99%
“…19 In addition, authors use perception when they study common convictions. Two examples are electronic cigarette safety 20 and cardiovascular health. 21 Since 1889, Acta Physiologica is the place for the honest yet fair scientific discourse of another form of perception, namely misunderstandings and "misperception" (see [22][23][24].…”
Section: E X a C T A Perceptionmentioning
confidence: 99%
“…Danlou tablet is a commercially available traditional Chinese medicine composed of 10 herbs. Exposure to secondhand tobacco smoke that contains nicotine can lead to severe health consequences, such as an increased risk of vascular dysfunction (Whitehead et al, 2021). Md Salleh et al reported that Piper sarmentosum Roxb.…”
Section: Editorial On the Research Topic Medicinal Plants In The Trea...mentioning
confidence: 99%